Electroactive microorganisms in mouse feces. (1st January 2021) - Rago, Laura; Popp, Denny; Heiker, John T.; Harnisch, Falk
Highlights: Electrochemical enrichment of mouse gut microbiome samples in bioelectrochemical systems. Anodic electroactive biofilm formation with a current production of 122±23 µA cm −2 . Anodic biofilm study using next generation sequencing and whole genome sequencing. Electroactive anodic enrichment of the current producing shigella flexneri 2a str. 301 . Abstract: The gut microbiome is not only an indicator of different pathologies, but it also influences metabolism and overall health of the host. Recently, microorganisms inherent to the gut microbiome, such as Listeria monocytogenes, Enterococcus faecalis and Clostridium cochlearium, were demonstrated to be electroactive, i.e. to perform extracellular electron transfer (EET). To further explore the presence of electroactive microorganisms in the gut microbiome electrochemical enrichment starting from mouse feces was performed. Open circuit, abiotic and autoclaved inoculum controls were run in parallel. A maximum current density of 122±23 µA cm −2 at low coulombic efficiency ( ̴1%) was achieved. The presence of biofilms at the anode and microbial electrochemical activity with a formal potential of EET of 0.23±0.01 V vs. Ag/AgCl sat. KCl was demonstrated using fluorescence microscopy and cyclic voltammetry. The 16S rRNA gene sequencing and PCR-free Nanopore sequencing showed the enrichment and dominance of Shigella flexneri . Graphical abstract: Image, graphical abstract